Tracking distance in division I men`s soccer: A comparison of global positioning systems - Huggins, R. A.; Willis, L. R.; Pryor, R. R.; Stearns, R. L.; DeMartini, J. K.; Johnson, E. C.; Pagnotta, K. D.; Lopez, R. M.; Casa, D. J. (Journal of Athletic Training, 2012)
Context: Calculating distance covered (DC)during team sports such as soccer is important to athletic trainers, coaches, and researchers when estimating or obtaining specific training volumes, athletic performances and rehabilitation goals. Previously this calculation of DC has proven difficult to obtain. Due to recent technological advances in the area of global positioning systems (GPS), the ability to measure distance in a team sport setting is now feasible. Currently, no research exists comparing different GPS measurement devices during Division I soccer. Objective: The purpose of this observational research was to describe the accuracy and compare two common GPS devices currently on the market (one less expensive$300/unit, and one expensive $2000/unit), used for quantifying exercise distance. Design: Observational field research. Setting: Outdoor soccer field. Patients or Other Participants: Twenty-one male NCAA Division I soccer players (age, 20± 1y; height, 187.5± 2cm; mass, 76.2± 5.6kg) Interventions: Participants completed six practices (98.9± 21.9min) and one game(113 min)on a standard grass soccer field. DC was collected using two different GPS devices, the less expensive Timex Global Trainer(GT) and the more expensive Catapult Minimax(MM). Additionally, accuracy was determined in a separate pilot testing session on a standard outdoor running track with all subjects running in the innermost lane. Main Outcome Measure: Paired sample t-tests were performed to analyze differences between mean DC as measured by both GPS devices. Alpha level was set at 0.05 a priori. Results: The accuracy of GT was (-0.02km; 95%CI -0.09 to 0.05) and MM was (0.01km; 95%CI -0.05 to 0.07). The DC measured with the two devices was similar (p = 0.11). Mean total DC for the six practices, one game, and combined practices and game as indicated by the GT was (10.0± 2.34km, 11.15± 3.73km, 10.17± 2.60km) respectively, and for MM (9.30± 2.35km, 11.27± 5.54km, 9.60± 3.07km). The % change between MM and GT were (-7.5, 1.0, -5.9%) for practices, game, and practice/game combined. MM-GT mean differences for DC in practice, game and practice/game combined were (-0.70± 0.66km,p <.05; 0.12 ± 2.05km, p = 0.84; -0.56± 1.02km; p <.05), respectively. Correlations between the devices for practice, game and practice/game combined were r2=(0.96, 0.98, and 0.93), respectively. Conclusion: The distances reported by the two devices were similar during the game, however during practice and practice/game combined comparisons, the devices were found to be significantly different. It should be noted that clinically the differences between the two devices are very small indicating that they are useful measurement tools for determining distance, performance and training volume.